Tissue adaptation to metabolic stress: insights from SUMOylation - Xie, Hao; Liu, Xin; Li, Shuo; Wang, Ming; Li, Ying; Chen, Ting; Li, Linwei; Wang, Faxi; Xiao, Xuan (Frontiers in Endocrinology, 2024)
Post-translational modification (PTM) plays a crucial role in adaptation of mammals to environmental changes, enabling them to survive in stressful situations. One such PTM is SUMO modification, which is evolutionarily conserved. It involves the covalent and reversible attachment of a small ubiquitin-like modifier (SUMO) to lysine (Lys) residues in the target protein. SUMOylation regulates various functions, including cell proliferation, differentiation, apoptosis, senescence, and maintenance of specific cellular activities. It achieves this by influencing protein-protein interactions, subcellular localization, protein stability, and DNA binding activity. Mounting evidence suggests that SUMOylation is implicated in the pathogenesis of metabolic disorders such as obesity, insulin resistance, and fatty liver. This review aims to provide an overview of the role of SUMOylation in regulating tissue adaptation to metabolic stress. Recent advancements in spectroscopic techniques have shed light on potential targets of SUMOylation and the underlying regulatory mechanisms have been elucidated, laying the theoretical foundation for the development of targeted SUMOylation interventions for metabolic syndrome while minimizing side effects.